Arts in Science: ‘Painting’ Health Allied Senior High School Students’ Meaningful Learning Engagement - Lainez, Buen Euleen V.; Dolendo, Russel Dustin R.; Agonoy, Jamie Marie Reynielle D.; Bargo, Rica Madeleine B.; Yumang, Ivhan Miles S.; Dizon, Mary Angel Adelle B.; Chua, Zeth Maverick Y.; Salayo, Juland D. (Utamax : Journal of Ultimate Research and Trends in Education, 2021)
The education system acknowledges the relevance and impact of arts in exploring students' different skills and competencies. However, most of the learners remain bias on the purpose and essence of art-based activities since most of the strands offered in senior high school are academically designed through the K-12 program, which guides and prepares incoming college students in choosing their career path. Hence, this study attempted to determine the vital role of arts-based instructional approaches to enrich students' learning in one selected catholic Senior High school in Manila, Philippines. Applying a qualitative approach through intensive interviews, 15 Health Allied students participated in this study. Results revealed that arts are highly integrated with the delivery of the different lessons of the involved strand. Moreover, arts proved that they have solid and influential roles in improving students' quality of learning. Furthermore, the impact and relevance of arts as an instructional approach supports the learning process of health allied students. Thus, this research informs and guides the teachers and students on the importance and impact of art as an overlooked field in education that maximizes one's potentials.